If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -1)(8 + -1x) = 0 Reorder the terms: (-1 + 2x)(8 + -1x) = 0 Multiply (-1 + 2x) * (8 + -1x) (-1(8 + -1x) + 2x * (8 + -1x)) = 0 ((8 * -1 + -1x * -1) + 2x * (8 + -1x)) = 0 ((-8 + 1x) + 2x * (8 + -1x)) = 0 (-8 + 1x + (8 * 2x + -1x * 2x)) = 0 (-8 + 1x + (16x + -2x2)) = 0 Combine like terms: 1x + 16x = 17x (-8 + 17x + -2x2) = 0 Solving -8 + 17x + -2x2 = 0 Solving for variable 'x'. Factor a trinomial. (-8 + x)(1 + -2x) = 0Subproblem 1
Set the factor '(-8 + x)' equal to zero and attempt to solve: Simplifying -8 + x = 0 Solving -8 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + x = 0 + 8 x = 0 + 8 Combine like terms: 0 + 8 = 8 x = 8 Simplifying x = 8Subproblem 2
Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5Solution
x = {8, 0.5}
| 2x-8x-44=100 | | 5(3z-1)-2(z+1)=10(z+1) | | 2a-3a=7-6a+4-11 | | 14x^3-38x^2+44x-15=0 | | x-9=87 | | friends+fake= | | 15n=-15 | | X+38+38=90 | | -73+2x+7x=98 | | 4(u+3)-3(3u-7)= | | 3(x-2)(x-2)+3=6x-12 | | -8(t-5)-(t+3)=10 | | p+7=7-6p | | X+45+35.8=90 | | 5/8c-8=2 | | 92+78=180 | | Y=300x^2-12 | | -41-5x+7x=19 | | (r-4)(r+1)+(r-4)(r+6)= | | 25x-30=-5 | | -x^2-24+45=0 | | X+16.5=90 | | 1.6(2x-1)=2(.4x+.7) | | 12=8n-(2n-3) | | -2y=-6-7x | | -2x-120+12x=40 | | lgx^3+2lgx^2-14=0 | | 42=1(z-3) | | b^2+13b+31=b-5 | | 0.4(4z+7)+2.8=0.6(4z-4) | | 20x+10y=1420 | | 5a^2+10a=0 |